Análise crítica-reflexiva sobre minha formação médica - Sukadolnik, Jane Farias (Universidade Federal de São Carlos, 2022)
The aim of this study is to present, by way of a critical narrative, my reflections on the problem-based learning teaching method adopted by the Department of Medicine at the Federal University of São Carlos, as well as aspects of the curriculum and the challenges I faced in the course of my medical education. It also introduces considerations about how I evolved during the six years of my undergraduate training in Medicine, insofar as, little by little, I managed to surmount my own limitations during this journey.
Critical-reflective analysis of my medical education
Keywords: Metodologia de ensino; Aprendizagem baseada em problemas; Educação médica; Teaching methodology; Problem-based learning; Medical education; CIENCIAS HUMANAS::EDUCACAO::CURRICULO